Treatment of Late Infective Prosthetic Endocarditis Complicated by Cerebral Infarction with Vegetations: Pharmacotherapeutic Approach (Case Report) - Popov, Volodymyr V.; Khoroshkovata, Olena V.; Bolshak, Oleksandr O.; Boukarim, Valery Zh.; Yuvchyk, Olena V.; Pukas, Kateryna V.; Fedkiv, Svitlana V. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Prosthetic endocarditis is a serious complication in a long term. Vegetation as a thromboembolic complication leads to neurologic deficit varying in severity. Case description. A 35-year-old female patient F. underwent surgical treatment at the Department of Surgical Treatment of Acquired Heart Diseases of the National Amosov Institute of Cardiovascular Surgery on September 07, 2016: aortic valve replacement with wrapping tape operation II. The patient was discharged from the hospital on the 9th day after surgery in a satisfactory condition. On November 20, 2019, the patient was admitted to the Institute with the diagnosis of late infective prosthetic aortic valve endocarditis, status post aortic valve replacement and wrapping tape operation in 2016, first-degree atrioventricular block, cerebral infarctions in multiple locations with hemorrhagic transformation, with aphasia elements, ataxia, right-sided pyramidal insufficiency and suspected meningitis. After 21 days of drug therapy, the patient responded to treatment successfully and was discharged from the hospital in a satisfactory condition without surgical treatment. Conclusions. Taking into consideration the serious condition of the patient, timely and carefully selected drug therapy can be the correct solution for the treatment of patients with late infective endocarditis. Thus, surgery is not always the treatment of choice.